IMPLEMENTATION OF ELECTRONIC CERTIFICATES IN MINIMIZING DOCUMENT DAMAGE IN PROBOLINGGO - Marwiyah, Siti; Maksin, Mastina; Citra, Lovita Adelia (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This article aims to find out how the Minister of ATR/Head of National Land Affairs Regulation No. 3 of 2023 is implemented regarding electronic certificate services in Probolinggo City, as well as to find out what the impact is in minimizing physical damage to documents on land certificates. Electronic certificates are expected to replace physical certificates which are vulnerable to damage, loss and forgery. The method used in this research is a qualitative approach with a case study at the Probolinggo City Land Office. Data was obtained through interviews with relevant officers, as well as surveys of land service users. The research results show that although electronic certificates can reduce the risk of physical damage to documents, there are still several obstacles in their implementation, such as limited technological infrastructure and uneven public understanding. Despite this, the majority of service users expressed a high level of satisfaction with the convenience and security offered by the electronic certificate system. The officers involved in this agency fully support this policy transformation. This research can recommend increasing outreach to the community and strengthening supporting infrastructure to maximize the benefits of electronic certificates in the future.